'THE BEAUTY OF A SICK ROOM': FAMILY CARE FOR THE DYING IN THE ENGLISH UPPER AND MIDDLE CLASS HOME c. 1840-c. 1890. (1st October 2013) - Helm, David
<x xml:space="preserve">Abstract</x> With the standard of care provided by hospitals and nursing homes to those nearing the end of their lives in Britain the subject of much concern and when increasing numbers of people would like to die at home, it is a timely moment to consider end of life care in the 19th century, when death at home was the norm and families had a leading role in providing care. This was also a period of change that laid the foundations for the 20th century model of hospital-centred palliative care. The article examines the experiences of middle and upper class carers, the objectives of care, including the importance of spiritual care, and the practicalities of providing care in the home. It also considers the support available to through informal networks of extended family, friends and neighbours and suggests aspects of care that may still have relevance to palliative care practice today.